Recycling of spent lithium-ion batteries. A study on the separation of manganese from cobalt, nickel and lithium in sulfuric media using solvent extraction. - Sherzot, Azimov (My University, 2020)
Manganese is an important alloying element that aids in the transformation of iron into steel. The steel industry consumes up to 90% of manganese globally, and it is expected that the expanding market for key non-metallurgical uses such as battery cathodes will have an increasing influence on its world market. Recycling in the steel and lithium-ion battery (LiB) sectors plays a critical role in meeting these needs. Solvent extraction for manganese recovery has been widely investigated to address this problem. However, there are drawbacks to this strategy, such as the co-extraction of metals and the infrequent consideration of the interplay of numerous factors that impact the metal extraction process. In this work, solvent extraction was utilized to improve manganese (Mn) extraction, reduce cobalt (Co) co-extraction, and eliminate high concentration contaminants like copper (Cu) and aluminum (Al) from spent (LiB) solution. Further, through the design of experiments and response surface methodology, it can be possible to identify and enhance influencing factors for manganese extraction by combining various variables. The best conditions for the extraction stage were found to be pH = 3.2, an O:A ratio of 1:1, and 0.5 M bis(2-Ethylhexyl) phosphoric acid (D2EHPA) with 15 minutes of contact time in this study. Mn extraction reached almost 89 % in a single extraction stage, with co-extraction of Co 2.5 %, which was then eliminated in two scrubbing stages. The optimal scrubbing stage operation conditions were discovered to be 6 g/L Mn (scrubbing solution – MnSO4.H2O), an O:A ratio of 1:1, and a contact time of 20 minutes. The ideal parameters for the stripping operation were determined to be 0.5 M sulfuric acid (H2SO4), an O:A ratio of 1:1, and a contact time of 15 minutes.
Keywords: solvent extraction; manganese; Li-ion batteries; D2EHPA; design of experiments